The concept of resilience based on the Shafi’i school of thought: exploring key themes for developing halal ecosystem - Rahim, Siti Majidah; Hashim, Norkhairiah (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
The concept of resilience has gained growing significance in the discourse surrounding the development of a sustainable and responsive halal ecosystem. As the global halal industry continues to expand, it faces significant challenges, and there is an urgent need to ensure long term integrity and continuity through a resilient halal ecosystem. In this context, the concept of a halal ecosystem emerges as an area that demands such an integrated approach. Therefore, the Shafi’i school of thought offers a profound jurisprudential foundation. To address these concerns, the primary objective of this study is to explore key themes within the Shafi’i school of thought that can serve as jurisprudential and ethical guiding principles for strengthening a resilient halal ecosystem. Employing a qualitative methodology, the study conducts a structured review of both classical legal texts and contemporary scholarly literature on the definition of resilience, halal governance, sustainability, and Islamic legal theory. This paper proposes an integrated framework based on the Shafi’i school of thought to develop a resilient halal ecosystem that is both jurisprudentially sound and morally robust. An integrated framework of six behavioural attributes based on the Organisational Resilience Model (ORM) and eight Islamic values are identified. The study highlights how the systematic methodology and ethical vision of the Shafi’i school of thought can shape a more accountable, spiritually aligned, and socially sustainable halal ecosystem.